Struggling for Self-Reliance: Four case studies of Australian Regional Force Projection in the late 1980s and the 1990s - Green, Bob (Canberra ANU Press, 2008)
Military force projection is the self-reliant capacity to strike from mainland ports, bases and airfields to protect Australia$1 (Bs sovereignty as well as more distant national interests. Force projection is not just a flex of military muscle in times of emergency or the act of dispatching forces. It is a cycle of force preparation, command, deployment, protection, employment, sustainment, rotation, redeployment and reconstitution. If the Australian Defence Force consistently gets this cycle wrong, then there is something wrong with Australia$1 (Bs defence. This monograph is a force projection audit of four Australian regional force projections in the late 1980s and the 1990s$1 (Bvalid measures of competence. It concludes that Australia is running out of luck and time. The Rudd Government has commissioned a new Defence White paper. This monograph is Exhibit A for changes
English
Keywords: Military history; australia; case studies; armed forces; national security; defenses; Bougainville Island; East Timor; Fiji; History of Bougainville; Power projection